A new perspective on cardiovascular drift during prolonged exercise - Amine Souissi (9931616) (2021)
Prolonged exercise induces cardiovascular drift, which is characterized by decreasing mean arterial pressure (MAP), stroke volume and heart rate increase. Cardiovascular drift has been debated for a long time. Although the exact mechanisms underlying cardiovascular drift are still unknown, two theories have been proposed. The first is that increased skin blood flow displaces blood volume from central circulation to the periphery, which reduces stroke volume. According to this theory, the rise in heart rate is presumably responding to the drop in stroke volume and MAP. The alternative theory is that an increase in heart rate is due to an increase in sympathetic nervous activity causing reducing time at diastole, and therefore stroke volume. It may be difficult to determine a single robust factor accounting for cardiovascular drift, due to the broad range of circumstances. The primary focus of this review is to elucidate our understanding of cardiovascular drift during prolonged exercise through nitric oxide and force-frequency relationship. We highlight for the very first time that cardiovascular drift (in some conditions and within a specific time period) may be considered as a protective strategy against potential damage that could be induced by the intense and prolonged contraction of the myocardium. Other Information Published in: Life Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.lfs.2021.120109